Improving Student Engagement and Learning Outcomes Through a Multi-Platform Gamification Ecosystem - Adhar; Najamuddin Mahmud; Satya; Muh. Wahyu; Andi Muhammad Aidil Hamid; Muh. Reza Fahrezi Iwan (Fakultas Teknik, Universitas Negeri Makassar, 2026)
Purpose – Theoretical courses such as Introduction to Education are often perceived by vocational education students, including those in the Automotive Engineering Education (PTO) program, as boring and disconnected from their practical orientation, resulting in low classroom engagement. This study aims to examine the improvement in student engagement and learning outcomes in the Introduction to Education course through the implementation of a multi-platform gamification ecosystem (Quizizz, Kahoot, Mentimeter, and Wordwall). Methods – This study employed the Kemmis & McTaggart model of Classroom Action Research (CAR), conducted in two cycles. The research subjects were 35 undergraduate students in the Automotive Engineering Education program enrolled in the Introduction to Education course. Findings – The implementation of the multi-platform gamification ecosystem increased student engagement from the “Low Engagement” category in the pre-cycle to “Highly Active” in Cycle II. The average percentage of student engagement increased from 52.4% (pre-cycle) to 71.8% (Cycle I), reaching 88.6% (Cycle II). Classical mastery of cognitive learning outcomes also increased, from 45.7% in the pre-cycle to 74.3% in Cycle I and 91.4% in Cycle II. Research implications – Within the limits of this classroom action research, the findings suggest that integrating varied gamification platforms may help reduce student boredom in theoretical courses and support a shift from passive-transactional toward more active, collaborative learning. As the findings are drawn from a single classroom over two cycles, they should be interpreted as context-specific rather than generalizable, and further studies across different settings are needed to confirm these patterns. Originality – While prior studies have largely examined single gamification platforms in isolation, this study contributes a context-specific instructional model that combines Quizizz, Kahoot, Mentimeter, and Wordwall synchronously and asynchronously within a single theoretical vocational education course, an integration pattern that remains underexplored in the vocational teacher education literature.